(Dis)Abling Translation and Tourism Studies (Altre Modernità, 2019)
This article will investigate the ways in which disability, meant both as a scientific field of enquiry and as a real-life issue our society is called to confront with, affects tourism and translation not only at the level of practice but also at a theoretical and methodological level. By assuming disability as a concern for all in everyday life, this issue takes on an urgency that triggers thought and action as few other social andcultural topics do nowadays. Hence, the article will provide a preliminary—and by no means exhaustive— overview of the historical representation of disability and analyse its impact on both Tourism and Translation Studies. No empirical case study will be presented to explore this impact, as the article aims instead to go beyond specific investigations of the strategies applied to cater for the needs of people with disabilities, which are in fact flourishing in Tourism and Translation Studies. However salutary this development may be considered, there is a need to enlarge the spectrum of enquiry beyond the specificity of case studies, and investigate the complex interplay between practice and theory in the fields of Disability, Tourism and Translation Studies.